Peran Pengurus Panti Dalam Mencegah Kenakalan Remaja (Studi Kasus Panti Asuhan Sinar Melati Yogyakarta) - Basuki, Arifin; Kurnia, Heri (Universitas Cokroaminoto Yogyakarta, 2022)
The purpose of this research is to examine the disgraceful behavior that is often carried out by foster children at the Sinar Melati Orphanage, as well as examine the role of the administrators in preventing it. In addition, this study aims to determine the factors that influence preventing this behavior in foster children. The research method used is qualitative research with data collection techniques through interviews and observation. Based on the results of the study, it was found that administrators have an important role in preventing dishonorable behavior towards foster children and they also help guide and foster foster children to become more compliant with applicable rules.